A Causality Analysis on Economy-Energy-Climate of Developing Countries: Focusing on the Effects of Climate-Related Development Finance - Lee, Minjoo; Lim, Jae-Bin (Journal of Korea Planning Association, 2025)
The intensification of climate change has resulted in increased focus on the interconnectedness of various economic and social sectors in recent years. In particular, studies investigating the relationships between environment and various socio-economic factors have increased. These studies are similar to those pertaining to the environmental Kuznets curve (EKC) hypothesis, as well as 3E studies, which focus on the interconnections among economy, energy, and environment. This study aims to extend this 3E model by investigating the economic–energy–climate nexus in developing countries as well as the effects of climate cooperation and technological cooperation. Hence, we constructed a simultaneous equation model to analyze the causality among economic growth (Gross Domestic Product per capita), energy (renewable-energy consumption), and climate change (carbon emissions) in 127 developing countries from 2005 to 2019. We employed the System GMM method of dynamic panel analysis for an efficient estimation. The results were categorized into economic, energy, and climate models. The economic model shows that renewable-energy consumption promotes economic growth, whereas carbon emissions hinder it. The energy model indicates that both economic growth and carbon emissions adversely affect renewable-energy consumption. In the climate model, the EKC hypothesis for economic growth is validated, where renewable-energy consumption is shown to reduce carbon emissions. Furthermore, the interaction terms indicate that climate cooperation and technological cooperation positively affect economic growth and renewable-energy consumption, whereas they adversely affect carbon emissions, thus demonstrating the synergistic effects of these cooperations. KCI Citation Count: 0